Writing for designers - Kubie, Scott (Book Apart (Series) ;, 2018)
From product documentation to menu labels to marketing emails, writing for the web can feel challenging--even insurmountable. But it doesn't have to be that way! Whether you're new to writing or looking to hone your skills, Scott Kubie's guide will empower you to get organized and get going. Learn to scope and articulate writing assignments, build a repeatable workflow, and develop methods for productive editing, collaboration, version control, and delivery. Don't struggle with writing--get the writing done. WHAT ARE BRIEFS?Briefs are short guides to essential fundamentals, of-the-moment techniques, or deep nerdery on a single aspect of a topic. Whatever the book, you're only a quick break away from learning vital, practical know-how. Now available in paperback via our print-on-demand service.